1997
DOI: 10.1093/dnares/4.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Arabidopsis thaliana Chromosome 5. I. Sequence Features of the 1.6 Mb Regions Covered by Twenty Physically Assigned P1 Clones

Abstract: A total of 20 P1 clones with an average insert size of 80 kb and each containing a marker(s) specifically mapped on chromosome 5 were isolated from a P1 library of the Arabidopsis thaliana genome, and their nucleotide sequences were determined according to a shotgun-based strategy and precisely located on the physical map of chromosome 5 separately constructed. The total length of the sequenced regions were summed up to 1,621,245 bp. By comparison with the sequences in protein and EST databases and analysis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Recombinant spinach TRX m (Schü rmann, 1995) at that concentration does not activate Arabidopsis DAHP synthase. Arabidopsis chloroplasts contain two TRX f isoforms (Sato et al, 1997). We have not yet shown which of these is the preferred reducing agent for DAHP synthase.…”
Section: Arabidopsis Dahp Synthase Requires Reduced Trx For Enzyme Acmentioning
confidence: 85%
“…Recombinant spinach TRX m (Schü rmann, 1995) at that concentration does not activate Arabidopsis DAHP synthase. Arabidopsis chloroplasts contain two TRX f isoforms (Sato et al, 1997). We have not yet shown which of these is the preferred reducing agent for DAHP synthase.…”
Section: Arabidopsis Dahp Synthase Requires Reduced Trx For Enzyme Acmentioning
confidence: 85%
“…The complete AtCDK8 open reading frame (At5g63610) was amplified by PCR from the P1 clone MBK5 (24), cloned into the acceptor vector ST1-blue (Invitrogen), and verified by restriction digestion and DNA sequencing. AtCDK8 was then subcloned into yeast vector pAS64F2 (33) to obtain pAS-AtCDK8.…”
Section: Methodsmentioning
confidence: 99%
“…In Arabidopsis, the catalytic subunit of PP2 (PP2Ac) is encoded by at least five genes, each of which appears to be expressed in all tissues albeit at different levels (Ariñ o et al, 1993;Casamayor et al, 1994; Pérez-Callejó n et al, 1998). Re-garding the regulatory subunits, three genes encoding the A 65-kD subunit (Slabas et al, 1994), two genes encoding the B subunit (Rundle et al, 1995;Corum et al, 1996), and one gene encoding the BЈЈ regulatory subunit (Sato et al, 1997) have been identified. In the last years, four isoforms of the BЈ regulatory subunit of PP2A have been described in Arabidopsis, named AtBЈ␣, AtBЈ␤, AtBЈ␥ (Latorre et al, 1997), and AtBЈ␦ (Haynes et al, 1999).…”
mentioning
confidence: 99%